2021
DOI: 10.1177/01634437211022730
|View full text |Cite|
|
Sign up to set email alerts
|

The criminal trial as a live event: Exploring how and why live blogs change the professional practices of judges, defence lawyers and prosecutors

Abstract: Live blogging from legal trials has become one of the most accessible ways in which the public can gain direct insight into legal proceedings, particularly in countries where television cameras are denied entry into the courtroom. Whilst live blogging constitutes an important way of ensuring the transparency and openness of legal processes and documents – a principle known as open justice and a key component of many democratic societies – the risks stemming from opening up the courts not only to more immediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Václav Janeek et al found significant differences in the performance of legal practitioners in the use of information technology in the provision of legal services, proposing the provision of specialized teaching and training for lawyers in information technology for legal services in order to improve their relevant competencies [14]. Flower, L. et al examined the forms and underlying logic of blogged legal trials, pointing out that, in order to gain the attention and interest of viewers, liveblogged legal trials are often exaggerated and performative in nature [15].…”
Section: Introductionmentioning
confidence: 99%
“…Václav Janeek et al found significant differences in the performance of legal practitioners in the use of information technology in the provision of legal services, proposing the provision of specialized teaching and training for lawyers in information technology for legal services in order to improve their relevant competencies [14]. Flower, L. et al examined the forms and underlying logic of blogged legal trials, pointing out that, in order to gain the attention and interest of viewers, liveblogged legal trials are often exaggerated and performative in nature [15].…”
Section: Introductionmentioning
confidence: 99%